The global revolution in public management: driving themes, missing links - Kettl, Donald F. (1997)
Since the late 1970s, a truly remarkable revolution has swept public management around the world. Understanding this revolution means sorting through three issues: the basic ideas of reform; the connections between the reforms and governmental processes, like budgeting and personnel; and the links between these proceses and governance. These reforms have proven surprisingly productive but, in the process, they have raised a new generation of fundamentally important issues that have been largely unexplored. - Reproduced
Keywords: Bureaucracy; Civil service; Public administration